Community Participation in Preschool Education of Ethiopia: the Case of South West Shewa Zone - Addisu Kumsa Megersa; Wudu Melese Tarekegne; Endalkachew Woldmariam (JETL (Journal of Education, Teaching and Learning), 2019)
The objective of this study was to examine the state of community participation in preschool education and factors affecting their participation in selected woredas of South West Shoa Zone. Survey research design was used. Data were collected from 192 preschool teachers, 58 preschool principals, 12 cluster supervisors 4 woreda education expert,   and 58 PTA members by using questionnaires, interview and focus group discussion. The findings of the study revealed that the participation of the community in preschool education is very low; the most common areas of community participation are cash contribution and participation in a meeting for the improvement of student behavior. Finally, the major factors identified are lack of awareness, failure to attend the meeting and failure to send their children to preschools. It is suggested that the preschools should be designed effective strategies of cooperation to work with the community in supporting preschools. In addition, continuous efforts should be made by preschools in the orientations and reorientation of community members about the objectives, scopes, principles, methods, and activities of preschool education.